2000
DOI: 10.1046/j.1365-2168.2000.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of inadvertent enterotomy during adhesiotomy

Abstract: The incidence of inadvertent enterotomy during reoperation is high. This adhesion-related complication has an impact on postoperative morbidity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
223
2
17

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(245 citation statements)
references
References 20 publications
3
223
2
17
Order By: Relevance
“…Yet, perhaps, it is precisely this group of patients who most require radical and complete surgery, not only to correct the resultant anatomical abnormalities created by the adhesions, but also to identify underlying pathology, such as cul de sac endometriosis, which may otherwise fail to be identified by incomplete dissection. While other authors have suggested that laparoscopic adhesiolysis is associated with very high rates of bowel injury of up to 25%, and that this should be a reason for reluctance to perform the operation [8,16], there was no bowel injury in the current series, suggesting in line with other series [17] that high complication rates are not inevitable. All of the patients in our series had postoperative flotation of the pelvic and abdominal organs, some with heparinised saline and most with 4% icodextrin (Adept, Shire).…”
Section: Discussionsupporting
confidence: 76%
“…Yet, perhaps, it is precisely this group of patients who most require radical and complete surgery, not only to correct the resultant anatomical abnormalities created by the adhesions, but also to identify underlying pathology, such as cul de sac endometriosis, which may otherwise fail to be identified by incomplete dissection. While other authors have suggested that laparoscopic adhesiolysis is associated with very high rates of bowel injury of up to 25%, and that this should be a reason for reluctance to perform the operation [8,16], there was no bowel injury in the current series, suggesting in line with other series [17] that high complication rates are not inevitable. All of the patients in our series had postoperative flotation of the pelvic and abdominal organs, some with heparinised saline and most with 4% icodextrin (Adept, Shire).…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, in the current study, accidental full-thickness enterotomy occurred in six patients (11%) despite the presence of an experienced laparoscopic surgeon. However, this still compares favorably with the 19% rate for inadvertent enterotomies during 270 relaparotomies in open surgery, as reported by van der Krabben et al [20]. The laparoscopic technique in itself should thus not be regarded as a risk factor for iatrogenic bowel injury.…”
Section: Discussionmentioning
confidence: 63%
“…Further, it is known that in reoperations, there is increased risk of bleeding and injury of adjacent organs (20). The secondary problems of intraabdominal adhesions formed after laparotomy may cause to economical costs (17,18). This study determined that the control group irrigated with SF showed more significant adhesion scores than the ID and HA groups.…”
Section: Discussionmentioning
confidence: 82%
“…Some of these problems may entail re-operation. It was indicated that abdominal adhesions formed after secondary laparotomy extended the laparoscopy, complicated the exploration and increased the possibility of iatrogenic intestinal diseases (17,18). It was reported that, in general surgery, 1% of all attempts and 3% of laparotomies are caused by peritoneal adhesions (19).…”
Section: Discussionmentioning
confidence: 99%